Analysis of the Relationship Between Learning Motivation and Critical Thinking Skills using The Problem-based Learning Model - Kusuma, Anindita Suliya Hangesti Mandra; Hidayati, Ermia (Journal of Classroom Action Research, 2025)
The learning of Basic Natural Sciences is still dominated by conventional discussion methods and one-way communication. The aim of this study is to fill a gap in the literature by examining the relationship between learning motivation and students' critical thinking skills in Basic Natural Sciences courses using the Problem-Based Learning (PBL) method. The study employs a correlational research method. Learning motivation is measured using the Attention, Relevance, Confidence, Satisfaction (ARCS) motivation questionnaire. Critical thinking skills are assessed through a test with indicators such as evaluating evidence, analyzing arguments, understanding implications and consequences, developing sound arguments, and understanding causation. Data analysis used in this research includes correlation analysis and regression analysis. The research results indicate a relationship between learning motivation and critical thinking skills. The correlation coefficient (r) value between learning motivation and critical thinking skills is 0.823, indicating a strong/high correlation. The relationship between learning motivation and critical thinking skills is positive. The coefficient of determination (r²) is 0.677 (67.7%), which means that 67.7% of the variability in critical thinking skills can be explained by learning motivation. The regression significance value confirms that the regression line equation can be used for predictions. The regression line equation for the relationship between learning motivation and critical thinking skills within the PBL model is .